2021
DOI: 10.3390/curroncol28030152
|View full text |Cite
|
Sign up to set email alerts
|

Early Reassessment of Total Metabolic Tumor Volume on FDG-PET/CT in Advanced Melanoma Patients Treated with Pembrolizumab Predicts Long-Term Outcome

Abstract: PD-1 Immune checkpoint inhibitors, such as Pembrolizumab, can have a durable beneficial therapeutic effect in patients with advanced melanoma. However, not all patients will benefit equally from these therapies, and (potentially life-threatening) immune-related adverse events may occur. In this study, we investigate the value of early response assessment by FDG-PET/CT as a biomarker for predicting survival. We identified all patients with advanced melanoma who were treated with Pembrolizumab in our medical cen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 20 publications
(22 reference statements)
1
4
0
Order By: Relevance
“…In the anti-PD1 group, PET parameters, such as EORTC, delta MTV and delta TLG, correlated with patients' outcomes at one year in most of the patients with PD according to these PET metrics. In 36 patients evaluated between 2 to 4 months after treatment by pembrolizumab monotherapy, Vermeulen et al found that PFS and OS were significantly longer in patients achieving a decreased/stable TMTV compared with those with increasing TMTV [23]. In our study, we found a similar result for PFS but not for OS, probably due to the limited size of our series of patients.…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…In the anti-PD1 group, PET parameters, such as EORTC, delta MTV and delta TLG, correlated with patients' outcomes at one year in most of the patients with PD according to these PET metrics. In 36 patients evaluated between 2 to 4 months after treatment by pembrolizumab monotherapy, Vermeulen et al found that PFS and OS were significantly longer in patients achieving a decreased/stable TMTV compared with those with increasing TMTV [23]. In our study, we found a similar result for PFS but not for OS, probably due to the limited size of our series of patients.…”
Section: Discussionsupporting
confidence: 61%
“…The analysis of tumor metabolic volume has been evidenced as a relevant tool in the evaluation of metastatic melanoma treated by ICI, allowing not only baseline outcome prognostication [18,26] but also accurate prediction of the response to treatment [20,22,23]. In a study on 85 melanoma patients treated with ICI, the metabolic tumor volume at first evaluation proved to be an independent prognostic factor for OS, along with the presence of central nervous system lesions [20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Employing the values of parameters in follow-up studies, Vermeulen et al reported an increase in total MTV on 2-to 4-month follow-up 2-[ 18 F]FDG PET/CT predicts worse OS and PFS [40]. There was a similar trend, although non-significant, for values on 5-to 6-month follow-up study [40]. Similarly, Nakamoto et al demonstrated that patients with higher MTV (≥23.44 cm 3 ) on the 3-month follow-up study have lower OS [41].…”
Section: Tablementioning
confidence: 99%
“… 6 Early total metabolic tumor volume evolution on 18 FDG-PET/CT, an interesting canulated parameter that can be easily (semi)-automatically determined, was found to be associated with long-term outcome in advanced melanoma patients with pembrolizumab treatment. 30 Evaluation by PET, however, has some limitations. First, the specificity can be low for a multifunctional radiotracer 18 FDG whose uptakes concern tumor and some inflammatory cells.…”
Section: Definition Of Immune-related Dr By Radiological Evaluation C...mentioning
confidence: 99%